Rural landscape characterization from the perspective of the tourist using online reviews: a case study of Yayou Gou village in Shandong, China - Zhuang, Qianda; Hussein, Mohd Kher; Mohd Ariffin, Noor Fazamimah; Mohd. Yunos, Mohd. Yazid; Chen, Shuzhen (Frontiers Media, 2022)
In the field of landscape characterization, it is difficult to obtain the tourists’ perceptions of a landscape. To overcome these drawbacks, online available reviews and comments from tourists can be utilized as an alternative way to characterize a landscape. This study examined the rural landscape characterization in Yayou Gou Village, which is a unique attraction in Shandong, China. A qualitative content analysis was undertaken on the tourists’ comments and reviews of Yayou Gou Village on tourist websites and social media platforms, including Qnar, Meituan, Ctrip, Dianping and Sina Microblog. NVivo 12 was used for the content analysis and qualitative coding. A variety of natural, cultural, and social, perceptual, and seasonal characteristics of a rural landscape, as well as facilities and infrastructure were revealed. Cultural and social landscape characters including performance landscape and festival activities, building, educational and home-stay landscape, diet landscape, and night landscape, which are obviously richer than other aspects in this rural village. Natural, perceptual, and seasonal landscape characters are not fully exploited for rural tourism and landscape. This study suggests that natural, cultural, and social rural landscape, and facility and infrastructure were influenced by spatial, seasonal, and perceptual dimensions. Suggestions for better landscape conservation and management can be acquired through the characterization process. This study provides an innovative approach for landscape characterization with online review data from various tourists. It demonstrates that online social media data contain abundant information about the landscape that they have visited and could be well used to explore the landscape’s characteristics in rural areas.